Pemaknaan Subjektif Pemuda Kota Yogyakarta mengenai Kepemilikan Rumah - Yuninda, Rahma (Universitas Gadjah Mada, 2024)
Youth in their maturation process are constructed through three stages of transition, one of which is having their own home. However, in the context of Yogyakarta City, the transformation of urban space that occurs is increasingly leading to tourism gentrification. This condition results in land scarcity and high land prices in Yogyakarta City. This study aims to determine the subjective meaning of Yogyakarta City youth regarding home ownership. This study uses a qualitative method involving four informants who are Yogyakarta City youth with certain criteria, namely based on status (students or fresh graduates), coming from different social classes (upper middle social class and lower middle social class), and considering gender aspects (male and female). Data collection was carried out through in-depth semi-structured interviews and supplemented with literature studies through relevant studies. The results of the study show that having your own home is still a reference for maturity for youth, but empirically not all can go through this transition smoothly. In addition, social class and gender aspects also influence the subjective meaning of youth regarding home ownership.